Scientific basis for standardization of fetal head measurements by ultrasound: a reproducibility study - Napolitano, R; Donadono, V; Ohuma, E; Knight, C; Wanyonyi, S; Kemp, B; Norris, T; Papageorghiou, A (John Wiley & Sons Ltd, 2016)
To compare the standard methods for ultrasound measurement of fetal head circumference (HC) and biparietal diameter (BPD) (outer-to-outer (BPDoo) vs outer-to-inner (BPDoi) caliper placement), and compare acquisition of these measurements in transthalamic (TT) vs transventricular (TV) planes.This study utilized ultrasound images acquired from women participating in the Oxford arm of the INTERGROWTH-21(st) Project. In the first phase of the study, BPDoo and BPDoi were measured on stored images. In the second phase, real-time measurements of BPD, occipitofrontal diameter (OFD) and HC in TT and TV planes were obtained by pairs of sonographers. Reproducibility of measurements made by the same (intraobserver) and by different (interobserver) sonographers, as well as the reproducibility of caliper placement and measurements obtained in different planes, was assessed using Bland-Altman plots.In Phase I, we analyzed ultrasound images of 108 singleton fetuses. The mean intraobserver and interobserver differences were < 2% (1.34 mm) and the 95% limits of agreement were < 5% (3 mm) for both BPDoo and BPDoi. Neither method for measuring BPD showed consistently better reproducibility. In Phase II, we analyzed ultrasound images of 100 different singleton fetuses. The mean intraobserver and interobserver differences were < 1% (2.26 mm) and the 95% limits of agreement were < 8% (14.45 mm) for all fetal head measurements obtained in TV and TT planes. Neither plane for measuring fetal head showed consistently better reproducibility. Measurement of HC using the ellipse facility was as reproducible as HC calculated from BPD and OFD. OFD by itself was the least reproducible of all fetal head measurements.Measurements of BPDoi and BPDoo are equally reproducible; however, we believe BPDoo should be used in clinical practice as it allows fetal HC to be measured and compared with neonatal HC. For all head measurements, TV and TT planes provide equally reproducible values at any gestational age, and HC values are similar in both planes. Fetal head measurement in the TT plane is preferable as international standards in this plane are available; however, measurements in the TV plane can be plotted on the same standards.